RETRACTED: Oroxylin a Inhibits the Protection of Bone Marrow Microenvironment on CML Cells Through CXCL12/CXCR4/P-gp Signaling Pathway - Cao, Hanbo; Li, Wenjun; Zhou, Yizhou; Tan, Renxiang; Yang, Yue; Zhou, You; Guo, Qinglong; Zhao, Li (Frontiers in Oncology, 2019)
Imatinib (IM) resistance could have significant impact on the survival time of the CML-patients treated with IM. Previous studies have shown that the protective effects of the bone marrow stroma cells (BMSCs) on CML cells are achieved by the secretion of CXCL12. The aim of this study was to investigate whether Oroxylin A could reverse the protective effect of BMSCs on CML cells and illuminate the underlying mechanisms. The results showed that CXCL12 could enhance the resistance potential of K562 and KU812 cells to IM by increasing the expression of CXCR4, thus promoting the translocation of β-catenin into nucleus and subsequently increasing the expression of P-gp in K562 and KU812 cells. What's more, IM resistance could also be partially reversed by CXCR4 siRNA transfection. Moreover, the reverse effect of IM resistance by Oroxylin A was demonstrated by the inhibition of β-catenin/P-gp pathway via the decrease of CXCR4 in vitro. The in vivo study also showed that Oroxylin A could decrease the expression of P-gp and β-catenin in mice bone marrow with low toxicity, which could be consistent with the mechanisms verified in vitro studies. In conclusion, all these results showed that Oroxylin A improved the sensitivity of K562 and KU812 cells to IM in BM microenvironment by decreasing the expression of CXCR4 and then inhibiting β-catenin/P-gp pathway.